Studying a study and testing a test : how to read the medical evidence - Riegelman, Richard K. (Philadelphia : Lippincott Williams & Wilkins, 2005)
Provides a concise, stepwise program that will help evaluate clinical studies, identify flaws in study design, interpret statistics, and apply evidence from clinical research to practice.
Introduction and flaw-catching exercise -- Types of studies and the M.A.A.R.I.E. framework -- Method -- Assignment -- Assessment -- Results -- Interpretation -- Extrapolation -- Randomized clinical trials -- Database research: nonconcurrent cohort studies -- Meta-analysis -- Questions to ask and flaw-catching exercises -- Method -- Assignment -- Assessment -- Results -- Interpretation -- Extrapolation -- Screening -- Questions to ask and flaw-catching exercises -- Method and assignment -- Assessment -- Results -- Interpretation and extrapolation -- Life expectancy -- Questions to ask and flaw-catching exercises -- Introduction and method -- Assignment -- Assessment -- Results -- Interpretation -- Extrapolation -- Questions to ask and Flaw-catching exercises -- Method -- Assignment -- Assessment -- Results -- Interpretation -- Extrapolation and questions to ask -- Basic principles -- Univariable analysis -- Bivariable analysis -- Multivariable analysis -- Selecting a statistic flowcharts.
Includes index.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Medical literature -- Evaluation; Medicine -- Research -- Evaluation; Biometry; Evidence-Based Medicine -- methods; Epidemiologic Methods; Research; Evidence-Based Medicine; Medical Literature Evaluation; Teaching Materials; Electronic books